Role of innovative technologies under the global zero emissions scenarios. (15th January 2016) - Tokimatsu, Koji; Konishi, Satoshi; Ishihara, Keiichi; Tezuka, Tetsuo; Yasuoka, Rieko; Nishio, Masahiro
Highlights: We modeled a zero emissions scenario based on the A1T scenario of IPCC-SRES. We conducted global modeling by minimizing costs of energy, biomass, and materials. A variety of advanced technology innovations were considered and incorporated. Results suggest that zero emissions scenario may be possible in this century. We revealed energy supply structure under the zero emissions scenarios. Abstract: This study investigated zero emissions scenarios with following two originalities compared to various existing studies. One is that we based on A1T society of SRES (Special Report on Emissions Scenario) of IPCC (Intergovernmental Panel on Climate Change) compared to existing studies on those of B1 or B2. The second one is that various innovative technologies were considered and incorporated, such as biomass energy with carbon capture and storage (BECCS), and advanced nuclear technologies including hydrogen or synfuel production. We conducted global modeling over the period 2010–2150 in which energy, materials, and biomass and foods supply costs were minimized by linear programming. We found following features of energy supply structure in A1T scenario. Since the electric demand in A1T scenario in 2100 is two times larger than the others, (1) renewable energy which solely produce electricity, nuclear, and fossil energy with CCS (FECCS) especially coal are main sources of electricity, (2) renewable which can supply heat, namely BECCS and geothermal, satisfies the sector, and (3) hydrogen from coal is introduced in transport sector. It can be concluded that the zero emission energy systems with global economic growth will be possible, by development and deployment of ambitious advanced energy technologies.